2020
DOI: 10.1111/iwj.13493
|View full text |Cite
|
Sign up to set email alerts
|

Heal or no heel: Outcomes of ischaemic heel ulcers following lower limb revascularization from a multi‐ethnic Asian Cohort in Singapore

Abstract: Ischaemic diabetic heel ulcers are difficult to treat and prognosis is often guarded. The aim was to document our outcome of treating heel ulcers following revascularization in a predominantly diabetic Asian cohort presenting with chronic limb threatening ischaemia from Singapore. Retrospective cohort study (n = 66, 66 limbs) over a 5‐year period. Data were collected from hospital electronic health records. Outcomes included time to healing, amputation free survival (AFS), and mortality. Minimum follow‐up peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…showed that, in the same setting in which the system was internally validated, those in stage 4 had a higher number of hospital admissions (mean of 3 vs. 2) and also higher overall costs (61,744 vs. 4653 US$) in comparison to those in stage 1. The three studies 140,142,143 that included mortality that had a clinical outcome were not able to show an association between this system and death at 1 year.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…showed that, in the same setting in which the system was internally validated, those in stage 4 had a higher number of hospital admissions (mean of 3 vs. 2) and also higher overall costs (61,744 vs. 4653 US$) in comparison to those in stage 1. The three studies 140,142,143 that included mortality that had a clinical outcome were not able to show an association between this system and death at 1 year.…”
Section: Resultsmentioning
confidence: 96%
“…The three studies 140,142,143 that included mortality that had a clinical outcome were not able to show an association between this system and death at 1 year. -25 of 32 costs, and quality of life.…”
Section: Stage/mentioning
confidence: 96%
See 1 more Smart Citation